MQIBS: An Efficient Post-Quantum Identity-based Signature from Multivariate Polynomials - Luyen, Le Van (Informatica, 2025)
Identity-based signature (IBS) is an important cryptographic primitive which allows authentication of a party’s public key without the need for certificates. In this paper, we construct a post-quantum provable identity-based signature scheme from multivariate polynomials. Our scheme is constructed from the sigma protocols with helper by Beullens at Eurocrypt 2020 and the Fiat-Shamir paradigm. Concrete choice of parameters shows that our scheme is more efficient than existing multivariate IBS schemes in terms of public key/signature sizes.